Success of endoscopic vacuum therapy for persistent anastomotic leak after esophagectomy – A case report. (March 2021) - Satoskar, Savni; Kashyap, Sarang; Benavides, Francisco; Jones, Robert; Angelico, Richard; Singhal, Vinay
Highlights: Endoscopic vacuum (endovac) therapy has excellent results for esophageal leaks. Endovac therapy has results superior to stents and can treat resistant leaks. Endovac therapy is well tolerated and feasible in the community setting. Commercial devices need to be manufactured to facilitate endovac placement. Abstract: Introduction: Endoscopic vacuum (endovac) therapy has shown excellent outcomes when used for esophageal anastomotic leaks. The results of endovac therapy are superior to those of other endoscopic therapies for esophageal leaks. Case presentation: We present a case of a 70-year-old male with esophageal adenocarcinoma who underwent Ivor Lewis esophagogastrectomy that was complicated by an esophageal leak. After failure of multiple endoscopic therapies (i.e. stents and clips), he responded well to endovac therapy. Discussion: Endovac therapy is extremely useful for the treatment of esophageal leaks. The widespread use of endovac therapy is feasible, even in smaller community hospitals. Conclusion: Endovac therapy is a valuable tool that can be used widely for the management of esophageal leaks. Commercially available devices need to be developed in order to facilitate endovac placement and exchange so that the procedure is less dependent on the skill of the operator.